The Correlation of Peer Conformity and Type of Smoking Behavior among Adolescents at a State Junior High School SMPN 3 Hamparan Perak Deli Serdang Regency - Nadya, Cici; Daulay, Wardiyah (Tradition and Modernity of Humanity, 2024)
The issue of peer conformity on smoking behavior significantly affect in individuals’ self-preservation to get acceptance and avoid rejection or critism from peers. These conformity factors cause individuals to engage in deviant behaviors, such as smoking. This research method aims to explore the correlation of peer conformity and the type of smoking behavior among adolescents at SMPN 3 Hamparan Perak, Deli Serdang Regency. This is a quantitative Research method with a descriptive correlational design conducted on 30 male adolescents ages 13 - 16 years old from May to June 2024. The data are collected by distributing questionnaires on peer conformity and the type of smoking behavior. The results of the statistical test using chi-square test with α=0.05 indicate a significant correlation between peer conformity and the type of smoking behavior among male adolescents at SMPN 3 Hamparan Perak (p-value = 0,034). Based on this research, it is recommended that the school conduct routine conseling sessions and promote anti-smoking campaigns to reduce the number of smoker among adolescents.